SOCIAL INTEGRATION OF MIGRANT WORKERS IN KERALA - Nimisha Sreedharan and V.Murale
Recently, Kerala has been experiencing a large inflow of migrant workers from various parts of India. Higher wages, better job opportunities and a dearth of local labor make Kerala a preferable job destination for people from other states. This is a conceptual paper on the Social Integration of Migrant Workers in Kerala. Its motive is to study the attitude of migrant workers towards the local population of Kerala and to check if their contribution towards the economy of Kerala is being duly recognized and accepted by the local people and also to determine the extent to which these workers are integrated towards the Kerala society. The study measures the attitude of migrant workers towards malayalees and examines the extent to which the attitude of migrant workers towards malayalees is influenced by factors like daily wages, their native state, marital status and interest to continue in Kerala. At the same time this study also measures the attitude of malayalees towards migrant workers and analyzes to what extent factors like occupation, gender and educational qualification influence their attitude towards migrant workers. Above all, the study measures the integration level of migrant workers towards the society, using the two dimensional model of the Ethnosizer, classifying the integration level into Assimilation, Integration, Marginalization and Separation, based on the commitment of migrant workers towards their host state (Kerala) and the commitment towards their state of origin.